γ-Al2O3 as acid catalyst for dehydration of glucose to 5-hydroxymethylfurfural - Fúnez Núñez, Inmaculada; García-Sancho, Cristina; Santamaría-González, José; Mérida-Robles, Josefa María; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (My University, 2015)
Currently, the search and development of sustainable feedstocks for chemicals derived from petrol have gained worldwide attraction because of the instability of the price of crude oil, the reduction of fossil oil reserves, and the environmental concerns associated to the greenhouse effect caused by CO2 emissions, being biomass one of the world’s most important renewable carbon sources. The major component of plant-derived biomass are carbohydrates, being of great importance to develop efficient and green approaches to their valorization by conversion into high value-added products. Thus, glucose can be transformed by dehydration into 5-hydroxymethylfurfural (HMF), which is a versatile and key intermediate for the production of a wide variety of biobased chemicals and it is attracting much attention in biofuels and chemical industry. Different catalytic systems have been evaluated for HMF production from C6 carbohydrates as glucose, mostly based on heterogeneous catalysis as alternative to the use of liquid mineral acids. On the other hand, the high surface area, large pore size and thermal and hydrothermal stabilities of some mesoporous solids make them suitable for many catalytic processes. In the present work, the dehydration of glucose to HMF has been evaluated by using different mesoporous γ-Al2O3 with acid, neutral or basic character, in a biphasic water–MIBK solvent system to avoid the HMF degradation and its possible reaction with the intermediates from glucose to give soluble polymers and humins or acetalization with glucose. Different experimental parameters, such as reaction temperature and time, as well as the addition of inorganic salts have been studied in order to reach the maximum HMF yield.
Keywords: Catálisis heterogénea; Alumina; Heterogeneous catalysis; Dehydration; Glucose; 5-Hydroxymethylfurfural